Time evolution of an atomic system in the presence of a time dependent electric field - Récamier, José; Paz, José Luis (Ciencia)
In this work we analyze the time evolution of an atomic system in the presence of an electromagnetic field. The interaction between the field and the system is modeled within the dipole approximation. As a zero approximation we first model the system with a harmonic oscillator and consider the field as classical. As is well known, in this case the quantal result is identical with the classical one. Then we model the system with a Morse oscillator which we expand keeping up to fourth order terms in the displacement coordinate. We compare the response of the system for different depths of the potential and different intensities of the field.